The Impact of Ancient Landscape Changes on the City Arrangement of the Early Shang Dynasty Capital Zhengzhou, Central China - Chen, Panpan; Lu, Peng; Yang, Shugang; Storozum, Michael; Yang, Ruixia; Tian, Yan; Wang, Hui; Wu, Qian; Xu, Junjie; Wang, Xia; Yan, Lijie; Zhai, Haiguo (Frontiers in Earth Science, 2021)
One of the ancient capital cities of the Shang dynasty (1766 – 1122 BCE) is buried underneath modern Zhengzhou city in Henan Province, China. While the ancient city was likely planned based on close consideration of the nearby landforms, there is no clear relationship between the current location of the rivers and topography. To better understand how the ancient Shang dynasty city of Zhengzhou was planned according to the local environment, we sampled sediments and measured stratigraphic exposure at excavations opened up throughout the remains of the ancient Shang dynasty city of Zhengzhou. We determined the ages of strata using OSL and the well documented ceramic chronology found in the cultural layers. Using these data, we reconstruct the regional landscape evolution through spatial interpolation and analysis. The results show that the different activity areas of the site have a close relationship with their environmental conditions. The palace was situated on higher ground and the different manual workshops were distributed along the ancient rivers. Our research is a significant step forward in understanding the relationship between environmental change and urban development.